Application of Prestressing Technology in Ultra-large LNG Storage Tanks at the "Green Energy Port" Project in Yancheng, Jiangsu Province - Zhichao Wang; Chaochen Wen; Yedong Jiang (预应力技术)
The Yancheng "Green Energy Port" is an important project planned under the National Natural Gas Production, Supply, Storage, and Sales System Construction and Interconnectivity program, and it is also the largest liquefied natural gas (LNG) reserve base currently under construction in China. In the first phase of the "Green Energy Port" project, 10 large LNG storage tanks were built, including 4 tanks with a capacity of 220,000 m3 and 6 tanks with a capacity of 270,000 m3 , the latter of which are currently the largest storage tanks with a single-tank capacity in the world. This report provides a brief introduction to the project context, outlines the layout of the prestressed system in the LNG storage tanks and the construction phases, and summarizes the critical tests for the prestress system in cryogenic tanks.